Artificial feeding of Ornithodoros fonsecai (Acari: Argasidae) with the anticoagulant Alsever - Castro-Santiago, Ana C.; Simons, Simone M.; Lima-Duarte, Leidiane; Camargo, Jaqueline V.; Machado, Rosangela Z.; André, Marco R.; Barros-Battesti, Darci M. (Entomological Communications, 2021)
Ornithodoros fonsecai is a species of argasid tick endemic to Brazil, described in the “São Miguel” cave located in the municipality of Bonito, state of Mato Grosso do Sul, central-western region of Brazil. The artificial feeding technique makes it possible to study the biology of hematophagous arthropods using artificial or natural membranes, as well as different types of blood and anticoagulants. Thus, the aim of the present study was to feed artificially O. fonsecai second instar (N2) nymphs with rabbit blood using parafilm membrane and the anticoagulant Alsever. Ninety percent of the total N2 nymphs engorged and molted to N3 nymphs between 27 and 30 days after feeding, indicating that the use of this anticoagulant is efficient for artificially feeding O. fonsecai N2 nymphs under laboratory conditions.